2020
DOI: 10.3390/coatings10010075
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoelectrochemical Properties from Mo-Doped TiO2 Nanotube Arrays Film

Abstract: Mo-doped TiO2 nanotube arrays are prepared successfully by a combined method of direct current (DC) magnetron sputtering and anodic oxidation. The doping amount of Mo can be modified by changing the number of molybdenum blocks on the Ti target while a Ti–Mo alloy film is prepared by magnetron sputtering on a metal Ti substrate, following a Mo-doped TiO2 nanotube array grown by anodization. Morphology test shows that the doping of Mo could inhibit the phase transition and growth of crystal of TiO2. X-ray photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…Moreover, almost identical Eg values were observed for all annealed samples independently of the applied potential. It should be emphasized that Eg values of annealed layers are much lower than those observed for pure anodic TiO2 generated under the same conditions [44], which is consistent with some previous findings showing that the doping of titania nanotubes with Mo results in a significant narrowing of Eg [26,27].…”
Section: Nanomaterials 2021 11 X For Peer Review 8 Of 15supporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, almost identical Eg values were observed for all annealed samples independently of the applied potential. It should be emphasized that Eg values of annealed layers are much lower than those observed for pure anodic TiO2 generated under the same conditions [44], which is consistent with some previous findings showing that the doping of titania nanotubes with Mo results in a significant narrowing of Eg [26,27].…”
Section: Nanomaterials 2021 11 X For Peer Review 8 Of 15supporting
confidence: 91%
“…Typically, as-received anodic TiO 2 layers fabricated on pure Ti and its alloys are amorphous [20,26,44]. Since for several applications, including photocatalysis and photoelectrochemical water splitting, the crystalline form of TiO 2 is mandatory, based on our previous research [44], we have annealed the anodized samples at 400 • C. The elemental analyses of non-annealed and annealed oxide layers (Figure 6a) show prominent peaks from Ti and Mo on both types of samples.…”
Section: Nanomaterials 2021 11 X For Peer Review 8 Of 15mentioning
confidence: 99%
See 1 more Smart Citation
“…Among several metal oxide photoelectrodes, titanium dioxide (TiO 2 ) has some distinctive properties including high corrosion resistance, good charge transfer, being environmentally benign, and exceptional stability, validating its use in several applications, especially solar cells and photoelectrochemical water splitting. However, some obstacles are yet to be resolved, such as limited efficiency of light utilization and the short lifetime of the photogenerated e – /h + pairs which leads to fast carriers recombination that adversely affects its performance in solar-energy-based systems. ,, To this end, fabricating 1D nanostructured photoelectrodes (nanotubes, nanowires, and nanorods) could provide high surface area, ensuring fast charge transfer with limited carriers recombination. ,, In this sense, one of the best approaches to develop a diversity of 1D nanostructures is electrochemical anodization, which is an efficient and low-cost technique. ,, However, doping was shown to boost the catalytic activity of TiO 2 and improve its overall performance. However, serious problems originated from some doping approaches that consider the interactions between dopant and defects and hide the essential interactions between both dopant and lattice. Thus, the effective doping approach should include suitable elements with definite ratios, which are crucial for the resultant photoresponse. ,,, Some recent studies of 1D nanostructures of mixed oxides showed a great improvement in photoelectrochemical systems. Roy et al reported the anodizing of Ti–Ru alloy to fabricate Ti–Ru–O mixed oxide nanotube arrays with enhanced photoelectrochemical water splitting .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the challenges of growing nanostructures on ternary systems, we successfully demonstrate the ability to design and fabricate Ti–Mo–Fe mixed oxide nanotube arrays via electrochemical anodization of Ti–Mo–Fe alloy in an organic-based electrolyte with low water content and study their properties as photoanodes for sustained water splitting. This particular system was chosen for the following reasons: (1) Mo 6+ should increase the electron density, thus enhancing the conductivity of the material. , (2) As a result of their close radii, Mo 6+ might replace Ti 4+ and act as electron shallow traps, which could improve the separation of photogenerated e – /h + pairs, resulting in an increase in the catalyst surface’s acidity and higher photocatalytic activity . (3) The high conductivity of Fe and its oxides could enhance the hole current toward the photoanode/electrolyte interface leading to enhance the rate of charge separation. , (4) Iron oxides might decrease the bulk recombination and provide good charge transportation between the interface layers …”
Section: Introductionmentioning
confidence: 99%